Fraud in BPJS According to Ethics and Health Law No. 17 Of 2023 - Kartika, Ronald Winardi; Nasser, M; Agus Suswantoro, Tri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
Background: Fraud in the National Health Insurance (JKN) program managed by BPJS Kesehatan poses a serious challenge to maintaining the sustainability of healthcare services in Indonesia. This study aims to analyze the forms of fraud, their impact on the healthcare system, and prevention strategies based on ethical and regulatory perspectives, specifically Health Law No. 17 of 2023 and Minister of Health Regulation No. 16 of 2019. Methodology: This study uses a normative legal approach with a descriptive-qualitative analysis method. Data were obtained through a literature review of applicable regulations, academic literature, and document analysis related to fraud in BPJS health. Primary legal sources include Health Law No. 17 of 2023 and various related regulations, while secondary sources consist of journal articles and research reports. The analysis was conducted by identifying fraud patterns, evaluating the effectiveness of supervision and administrative sanctions, and reviewing the role of technology in fraud mitigation. Results: Research shows that BPJS health fraud occurs due to weak supervision, minimal participant literacy regarding rights and obligations, and gaps in the claims and verification system. Implementing an information technology-based anti-fraud system, participant education, and increased oversight are strategic steps to minimize fraud. With a multidisciplinary approach, it is hoped that the JKN system can function optimally, ensure transparency, and increase the accountability of healthcare providers